2021
DOI: 10.1155/2021/6693960
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Oxidative Quality Characterization of Spray-Dried Omega-3-Enriched Milk Powder

Abstract: In the present study, fish oil (FO) and wall material were supplemented to milk to produce spray-dried powder (SDP). Furthermore, the mandate of the study was to enlighten the effect of spray-drying (SD) operating conditions on functional and oxidative quality of produced SDP samples. Purposefully, the cow milk was supplemented with 3% FO as omega-enriched source of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) for development of milk and FO blends (MFOBs). The lecithin was used as an emulsifier a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
1
0
0
Order By: Relevance
“…Rahim et al 21 showed that the fatty acid losses in SDM of CSO and FO were in the acceptable range at 170 °C. The results were consistent with Lavanya et al 15 ; Ali et al 51 and Rahim et al 39 , who established that there was no significant ( p > 0.05) effect of spray dryer operating conditions on the fatty acid composition.…”
Section: Resultssupporting
confidence: 91%
“…Rahim et al 21 showed that the fatty acid losses in SDM of CSO and FO were in the acceptable range at 170 °C. The results were consistent with Lavanya et al 15 ; Ali et al 51 and Rahim et al 39 , who established that there was no significant ( p > 0.05) effect of spray dryer operating conditions on the fatty acid composition.…”
Section: Resultssupporting
confidence: 91%